Neutral Lipopolyplexes for In Vivo Delivery of Conventional and Replicative RNA Vaccine - Federico Perche; Rudy Clemençon; Kai Schulze; Thomas Ebensen; Carlos A. Guzmán; Chantal Pichon (Elsevier, 2019)
Nucleic acid vaccination relies on injecting DNA or RNA coding antigen(s) to induce a protective immune response. RNA vaccination is being increasingly used in preclinical and clinical studies. However, few delivery systems have been reported for in vivo delivery of RNA of different sizes. Using a tripartite formulation with RNA, cationic polymer, and anionic liposomes, we were able to encapsulate RNA into neutral lipopolyplexes (LPPs). LPPs were stable in vitro and successfully delivered conventional RNA and replicative RNA to dendritic cells in cellulo. Their injection led to reporter gene expression in mice. Finally, administration of LPP-Replicon RNA (RepRNA) led to an adaptive immune response against the antigen coded by the RepRNA. Accordingly, LPPs may represent a universal formulation for RNA delivery. Keywords: mRNA delivery, self-amplifying RNA, splenic dendritic cells, targeting